Composite glass powder, preparation method thereof, silver-coated copper paste and solar cell

CN122977709APending Publication Date: 2026-10-27JA SOLAR TECH YANGZHOU
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611141479.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但此类方案中,磷/硼原子在玻璃熔制过程中已均匀分散于玻璃网络结构中,被玻璃网络束缚,难以与扩散的铜离子充分接触反应,捕获效率有限

Benefits of technology

[0025]本发明的复合玻璃粉具有核壳结构,所述复合玻璃粉包括内核玻璃粉和包覆在所述内核玻璃粉的表面上的外壳层,所述外壳层包含过渡金属硫族化合物和/或过渡金属磷族化合物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977709A_ABST
    Figure CN122977709A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of composite glass powder and its preparation method, silver-coated copper paste and solar cell, belong to solar cell field. Specifically, the composite glass powder of the present application has core-shell structure, the composite glass powder includes inner core glass powder and the shell layer on the surface of inner core glass powder, shell layer includes transition metal chalcogen compound and / or transition metal phosphorus compound. When silver-coated copper paste prepared based on the composite glass powder of the present application is applied in solar cell, the performance of anti-potential induced decay and long-term reliability of solar cell module are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composite glass powder and its preparation method, silver-coated copper paste, and solar cells, belonging to the field of solar cells. Background Technology

[0002] Silver-coated copper powder, as a substitute for pure silver powder in the conductive paste of the fine grid on the back of solar cells (synonymous with "photovoltaics"), can significantly reduce electrode costs.

[0003] For example, CN 104157331 A discloses a silver-coated copper paste for silicon solar cell electrodes and its preparation method. The silver-coated copper paste comprises micro-fine silver-coated copper powder, lead-free glass powder, organic carrier, and additives. The mass percentage of silver-coated copper powder in the paste is 75%-80%, the mass percentage of lead-free glass powder is 3%-10%, the mass percentage of organic carrier is 10%-15%, and the mass percentage of additives is 3%-10%. The micro-fine silver-coated copper powder is a spherical micro-fine metal powder with a copper core, a silver shell, and a copper-tin-silver alloy in the middle layer. The lead-free glass powder adopts a bismuth-silicon-boron-zinc-cerium-molybdenum glass system, with the following composition and mass percentage: Bi₂O₃ 60%-80%, SiO₂ 5%-10%, B₂O₃ 5%-10%, ZnO 5%-10%, CeO₂ 2%-6%, and MoO₃ 2%-6%. The softening temperature of the glass powder is 400-600℃. This conductive paste uses fine silver-coated copper powder as the conductive component, saving a large amount of silver powder and greatly reducing the raw material cost of the conductive paste.

[0004] However, existing silver-coated copper pastes suffer from severe copper ion migration problems during high-temperature sintering or in modules used outdoors for extended periods. Copper atoms diffuse to the surface and are oxidized into copper ions, which then migrate into the silicon substrate under the influence of an electric field, forming recombination centers and leading to cell efficiency degradation.

[0005] In the prior art, there are two main approaches to suppressing copper migration.

[0006] 1. Physical blocking solution.

[0007] This approach aims to physically block copper diffusion by optimizing the density of the silver layer or introducing an intermediate barrier layer (such as a nickel layer or an alumina layer) between the copper core and the silver layer. However, such approaches are complex to manufacture, and the barrier layer is prone to thermal stress cracks during high-temperature sintering, forming new diffusion channels. This passive defense is ineffective once it cracks.

[0008] 2. Chemical doping schemes.

[0009] This approach involves adding components such as P2O5 and B2O3 to the glass powder formulation. However, in this type of approach, the phosphorus / boron atoms are already uniformly dispersed in the glass network structure during the glass melting process. They are bound by the glass network and cannot fully contact and react with the diffused copper ions, resulting in limited capture efficiency. Summary of the Invention

[0010] [Technical Issues]

[0011] Therefore, there is an urgent need for a novel glass powder system that can actively, efficiently, and in situ capture copper ions without affecting conductivity.

[0012] On the other hand, there is an urgent need for a simple and cost-effective method for preparing glass powder and a method for preparing silver-coated copper paste.

[0013] [Technical Solution]

[0014] To address the aforementioned problems, one aspect of the present invention provides a composite glass powder having a core-shell structure, comprising a core glass powder and an outer shell layer covering the surface of the core glass powder, the outer shell layer comprising a transition metal chalcogenide and / or a transition metal phosphorus compound.

[0015] According to one embodiment of the present invention, a composite glass powder, The transition metal chalcogenide includes one or more selected from molybdenum disulfide (MoS2), tungsten disulfide (WS2), molybdenum diselenide (MoSe2), and tungsten diselenide (WSe2); And / or, The transition metal phosphorus compound includes one or more selected from tungsten phosphide (WP), molybdenum phosphide (MoP), cobalt phosphide (CoP), and nickel phosphide (NiP); And / or, The core glass powder is a lead-free glass powder comprising Bi2O3, B2O3, ZnO and SiO2.

[0016] According to one embodiment of the present invention, a composite glass powder, The mass of the outer shell layer is 1% to 10% of the mass of the core glass powder; And / or, The thickness of the outer shell layer is 10 nm to 200 nm.

[0017] According to one embodiment of the present invention, a composite glass powder, The softening point of the core glass powder is 400℃~600℃; And / or, The particle size D50 of the core glass powder is 1.0 μm to 3.0 μm; And / or, Based on the total mass of the core glass powder as 100%, the composition and mass fraction of each component of the core glass powder are as follows: Bi2O3 55%~75%, B2O3 8%~18%, ZnO 5%~15%, SiO2 3%~8%, TeO2 0%~20%, TiO2 2%~4%, Ga2O3 0.3%~5%, AlF3 2%~6%, MnO2 1%~6%, and additives 0%~4%, wherein the additives are one or more of CeO2 and MoO3.

[0018] Furthermore, to address the aforementioned problems, another aspect of the present invention provides a method for preparing composite glass powder according to the present invention, the method comprising the following steps: (1) Provide core glass powder; (2) The core glass powder is mixed with a transition metal chalcogenide and / or a transition metal phosphorus compound, so that the transition metal chalcogenide and / or the transition metal phosphorus compound adhere to the surface of the core glass powder, and then heat-treated in a nitrogen or inert gas atmosphere to obtain the composite glass powder with a core-shell structure. or, The core glass powder is dispersed in a solvent, and precursors of transition metal chalcogenides and / or transition metal phosphogenides are added. The precursors are then attached to the surface of the core glass powder by chemical deposition, followed by reduction heat treatment to obtain the composite glass powder with a core-shell structure.

[0019] According to an embodiment of the present invention, the core glass powder is prepared by the following method: the components of the core glass powder are mixed evenly, then heated to melt the components evenly to obtain a glass melt, the glass melt is then quenched to form glass fragments, and finally the glass fragments are ball-milled and sieved to obtain the core glass powder with the desired particle size. And / or, The transition metal chalcogenide and / or the transition metal phosphorus compound are mixed by ball milling to adhere to the surface of the core glass powder. The ball milling process conditions include: nitrogen or inert gas atmosphere, ball milling speed of 300 rpm to 500 rpm, and ball milling time of 2 h to 4 h. And / or, When transition metal chalcogenides and / or transition metal phospholipids are used as raw materials, the heat treatment temperature is 350℃~450℃ and the time is 30 min~60 min; when transition metal chalcogenides and / or transition metal phospholipids precursors are used as raw materials, the reduction heat treatment temperature is 350℃~450℃ and the time is 30 min~60 min.

[0020] In addition, to address the above-mentioned problems, another aspect of the present invention provides a silver-coated copper paste comprising composite glass powder, silver-coated copper powder, and an organic carrier according to the present invention.

[0021] According to one embodiment of the present invention, the silver-coated copper paste, with the total mass of the silver-coated copper paste being 100%, has the following mass percentages of each component: 75%~85% silver-coated copper powder, 2%~8% composite glass powder, and 12%~20% organic carrier.

[0022] According to one embodiment of the present invention, a silver-coated copper paste, The silver content in the silver-coated copper powder is 10% to 40% by mass. And / or, The particle size D50 of the silver-coated copper powder is 1 μm to 3 μm; And / or, The fineness of the silver-coated copper paste is less than or equal to 10 μm and the viscosity is 150 Pa·s to 250 Pa·s.

[0023] In addition, to address the above-mentioned problems, another aspect of the present invention provides a solar cell comprising electrodes prepared from silver-coated copper paste according to the present invention.

[0024] [Beneficial Effects]

[0025] The composite glass powder of the present invention has a core-shell structure, comprising a core glass powder and an outer shell layer covering the surface of the core glass powder, wherein the outer shell layer comprises a transition metal chalcogenide and / or a transition metal phosphorus compound.

[0026] Therefore, by using transition metal chalcogenides and / or transition metal phosphides with specific chemical activity as the outer shell layer of the composite glass powder, the present invention effectively suppresses the migration of copper to the silicon matrix.

[0027] Meanwhile, the outer shell material has good electrical conductivity and does not deteriorate the contact resistance.

[0028] Therefore, the silver-coated copper paste prepared using the core-shell structured composite glass powder of the present invention can significantly improve the resistance to potential-induced degradation (PID) and long-term reliability of photovoltaic modules while maintaining the minority carrier lifetime and photoelectric conversion efficiency of the cells.

[0029] On the other hand, the preparation method of the composite glass powder and the silver-coated copper paste containing it of the present invention is simple in process, has controllable cost, and can be effectively applied to solar cells. Attached Figure Description

[0030] For clarity, the accompanying drawings of this invention may not be actual scale figures, but rather exemplary schematic diagrams.

[0031] Figure 1 The composite glass powder and comparative glass powder of the present invention are characterized by high-temperature microscopic temperature points and patterns during the melting process.

[0032] Figure 2 A schematic diagram of the contact angles of the composite glass powder and comparative glass powder after they have completely melted onto a silicon substrate according to the present invention. Detailed Implementation

[0033] The present invention will be further illustrated below with reference to the accompanying drawings and embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0034] As used herein, the term "D50" refers to the particle size corresponding to 50% of the volumetric cumulative particle size distribution. D50 can be measured using methods known in the art, such as laser diffraction.

[0035] In this invention, unless otherwise specified, percentages expressed as "%" all represent mass percentages, i.e., "mass%".

[0036] Composite glass powder according to the present invention

[0037] One aspect of the present invention provides a composite glass powder having a core-shell structure, the composite glass powder comprising a core glass powder and an outer shell layer covering the surface of the core glass powder, the outer shell layer comprising a transition metal chalcogenide and / or a transition metal phosphorus compound.

[0038] <Outer Shell>

[0039] According to one embodiment of the composite glass powder of the present invention, the outer shell layer may comprise a transition metal chalcogenide and / or a transition metal phosphorus compound. Specifically, the outer shell layer may comprise a transition metal chalcogenide, the outer shell layer may comprise a transition metal phosphorus compound, or the outer shell layer may comprise both a transition metal chalcogenide and a transition metal phosphorus compound.

[0040] According to a specific embodiment of the present invention, the composite glass powder may include one or more of the transition metal chalcogenides selected from MoS2, WS2, MoSe2, and WSe2, preferably MoS2.

[0041] According to another specific embodiment of the present invention, the composite glass powder may include one or more transition metal phosphorus compounds selected from WP, MoP, CoP, and NiP, preferably WP.

[0042] This invention utilizes transition metal chalcogenide and / or phosphorus compounds with specific chemical activity, as described above, as the outer shell layer of the composite glass powder. The sulfur and / or phosphorus atoms in these compounds form strong chemical bonds with copper ions diffused from the silver-coated copper paste, thereby capturing and immobilizing copper ions in situ and effectively suppressing copper migration into the silicon substrate. Simultaneously, this outer shell layer material exhibits good electrical conductivity without deteriorating contact resistance.

[0043] According to one embodiment of the present invention, the composite glass powder contains no particular limitation on the morphology of the transition metal chalcogenide and transition metal phosphide compounds, but they can be in flake or granular form. For example, the transition metal chalcogenide and transition metal phosphide compounds can be in flake or granular form.

[0044] In a more preferred embodiment of the present invention, MoS2 is preferably in the form of sheets, thereby fully utilizing the physical barrier and chemical capture effects of its two-dimensional layered structure. In a more preferred embodiment of the present invention, WP is preferably in the form of nanoparticles, thereby ensuring a high specific surface area and sufficient exposure of active sites. However, the present invention does not exclude the use of MoS2 particles or WP sheet materials, as long as the function of chemical capture of copper ions can be achieved.

[0045] According to one embodiment of the present invention, the composite glass powder contains no particular limitation on the size of the transition metal chalcogenide and transition metal phosphide compounds, but they can be at the nanoscale. For example, the transition metal chalcogenide and transition metal phosphide compounds can be nanosheets or nanoparticles, etc.

[0046] According to one embodiment of the composite glass powder of the present invention, the thickness of the outer shell layer can be from 10 nm to 200 nm. For example, the thickness of the outer shell layer can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, etc. In a more preferred embodiment of the present invention, the thickness of the outer shell layer is preferably from 20 nm to 150 nm. When the thickness of the outer shell layer is too low, the outer shell layer is too thin, making it difficult to achieve the effect of chemically capturing diffused copper ions; when the thickness of the outer shell layer is too high, the effect of capturing diffused copper ions brought about by the outer shell layer no longer increases further, but a larger amount of transition metal compound is required to form the outer shell layer, thus potentially increasing the cost.

[0047] <Core Glass Powder>

[0048] According to one embodiment of the present invention, the composite glass powder may include core glass powder.

[0049] According to one embodiment of the present invention, the composite glass powder may be a lead-free glass powder comprising Bi2O3, B2O3, ZnO and SiO2.

[0050] Therefore, the core glass powder used in the core glass of this invention belongs to the lead-free Bi2O3-B2O3-ZnO system glass powder. This invention is an improvement upon this system of core glass powder. By forming the specific outer shell layer according to the invention as described above on the surface of the core glass powder of this system, the performance of the lead-free Bi2O3-B2O3-ZnO system glass powder in the conductive paste of the back grid and, in particular, in the electrodes for solar cells, can be improved.

[0051] According to a further embodiment of the composite glass powder of the present invention, additives may be added to the core glass powder, such as one or more selected from CeO2 and MoO3, and the core glass powder contains 0% to 4% additives based on 100% of the total mass of the core glass powder.

[0052] According to a specific embodiment of the composite glass powder of the present invention, the composition and mass fraction of the core glass powder, based on the total mass of the core glass powder as 100%, are as follows: Bi2O3 55%~75%, B2O3 8%~18%, ZnO 5%~15%, SiO2 3%~8%, TeO2 0%~20%, TiO2 2%~4%, Ga2O3 0.3%~5%, AlF3 2%~6%, MnO2 1%~6%, and additives 0%~4%, wherein the additives are one or more of CeO2 and MoO3.

[0053] According to one embodiment of the present invention, the softening point of the core glass powder can be 400°C to 600°C, preferably 400°C to 550°C, more preferably 450°C to 550°C, and even more preferably 450°C to 500°C.

[0054] According to one embodiment of the present invention, the composite glass powder has a particle size D50 of 1.0 μm to 3.0 μm, preferably 1.5 μm to 2.5 μm.

[0055] According to one embodiment of the composite glass powder of the present invention, the mass of the outer shell layer is 1% to 10% of the mass of the core glass powder. According to a preferred embodiment of the composite glass powder of the present invention, the mass of the outer shell layer can be 3% to 8% of the mass of the core glass powder. Exemplarily, the mass of the outer shell layer can be 4%, 5%, 6%, 7%, etc., of the mass of the core glass powder. When the content of the outer shell layer is too low, it is difficult to achieve the effect of chemically capturing diffused copper ions; when the content of the outer shell layer is too high, the corresponding content of the core glass powder is too low, and the production cost may also increase.

[0056] The method for preparing composite glass powder according to the present invention

[0057] Another aspect of the present invention provides a method for preparing composite glass powder according to the present invention, the method comprising the following steps: (1) Provide core glass powder; (2) Preparation of the outer shell layer (2.1) The core glass powder is mixed with a transition metal chalcogenide and / or a transition metal phosphorus compound, so that the transition metal chalcogenide and / or the transition metal phosphorus compound adhere to the surface of the core glass powder, and then heat-treated in a nitrogen or inert gas atmosphere to obtain the composite glass powder with a core-shell structure. or, (2.2) The core glass powder is dispersed in a solvent, and a precursor of a transition metal chalcogenide and / or a transition metal phosphide is added. The precursor is attached to the surface of the core glass powder by chemical deposition, and then a reduction heat treatment is performed to obtain the composite glass powder with a core-shell structure.

[0058] As described above, the method for preparing composite glass powder according to the present invention can prepare the glass powder according to the present invention as described above.

[0059] <Steps for forming the outer shell layer>

[0060] The following describes in detail the steps of forming the outer shell layer in the composite glass powder preparation method using ball milling (i.e., step (2.1) in the above preparation method, hereinafter referred to as the "dry method") and solvent (i.e., step (2.2) in the above preparation method, hereinafter referred to as the "wet method"), but the present invention is not limited thereto.

[0061] According to one embodiment of the present invention, a method for preparing composite glass powder involves mixing a core glass powder with a transition metal chalcogenide and / or a transition metal phosphide compound, causing the transition metal chalcogenide and / or transition metal phosphide compound to adhere to the surface of the core glass powder, followed by heat treatment under a nitrogen or inert gas atmosphere. This method uses transition metal chalcogenides and / or transition metal phosphides as raw materials to form a shell layer on the surface of the core glass powder, thereby obtaining a composite glass powder with a core-shell structure.

[0062] In the dry method described above, ball milling can be used to mix the transition metal chalcogenides and / or transition metal phosphogenides onto the surface of the core glass powder. The ball milling process conditions include: a nitrogen or inert gas atmosphere, a ball milling speed of 300 rpm to 500 rpm, and a ball milling time of 2 h to 4 h. Exemplarily, the ball milling speed can be 350 rpm, 400 rpm, 450 rpm, etc., and the ball milling time can be 2.5 h, 3.0 h, 3.5 h, etc.

[0063] In the dry method described above, the heat treatment temperature can be 350°C to 450°C, and the time can be 30 min to 60 min. For example, the heat treatment temperature can be 380°C, 400°C, 420°C, etc., and the heat treatment time can be 35 min, 40 min, 45 min, 50 min, 55 min, etc.

[0064] According to another embodiment of the present invention, a method for preparing composite glass powder involves dispersing core glass powder in a solvent and adding precursors of transition metal chalcogenides and / or transition metal phospholipids. The precursors are then deposited onto the surface of the core glass powder via chemical deposition, followed by reduction heat treatment. This method uses precursors of transition metal chalcogenides and / or transition metal phospholipids as raw materials to form an outer shell layer on the surface of the core glass powder, thereby obtaining a composite glass powder with a core-shell structure.

[0065] In the wet method described above, the reduction heat treatment temperature can be 350°C to 450°C, and the time can be 30 min to 60 min. For example, the reduction heat treatment temperature can be 380°C, 400°C, 420°C, etc., and the reduction heat treatment time can be 35 min, 40 min, 45 min, 50 min, 55 min, etc.

[0066] The composite glass powder meeting the requirements of the present invention can be obtained by using ball milling (dry method) and solvent (wet method) as described above according to the present invention. Furthermore, the preparation method according to the present invention is simple, cost-controllable, and the resulting composite glass powder can be effectively applied in the production of solar cells.

[0067] In contrast to the method of the present invention, simple physical mixing cannot obtain the composite glass powder according to the present invention. The reason is that simple physical mixing will lead to uneven distribution of chemically active components, inaccurate positioning and uneven distribution at the interface, and failure to form a continuous and effective capture barrier, thus failing to achieve the technical effect of the present invention.

[0068] <Steps for providing core glass powder>

[0069] According to one embodiment of the present invention, a method for preparing composite glass powder is provided, wherein the core glass powder can be prepared by the following method: mixing the components of the core glass powder evenly, then heating to melt the components evenly to obtain a glass melt, then quenching the glass melt to form glass fragments, and finally ball milling and sieving the glass fragments to obtain the core glass powder of the desired particle size, but the present invention is not limited thereto.

[0070] The following is a specific method for preparing the composite glass powder according to the present invention, illustrated by an example: Step 1: Grind all the raw materials used to prepare the glass powder in an agate mortar for 20 to 40 minutes to ensure thorough mixing. Then, place the mixture in a corundum crucible and place the crucible into a high-temperature electric furnace preheated to 1200°C to 1300°C. Melt the glass at this temperature for 0.5 to 2 hours, shaking the molten glass in the furnace every 25 to 35 minutes to ensure uniform melting of all components. Remove the crucible and quench the molten glass in deionized water. Collect the glass fragments, dry them, and then ball-mill them in a planetary ball mill. Sift the mixture to obtain the core glass powder of the desired particle size.

[0071] Step 2: Take the core glass powder obtained in Step 1, add transition metal chalcogenides and / or transition metal phosphides (e.g., nano-MoS2 flakes or nano-WP particles), place it in a ball mill, and ball mill at 300 rpm to 500 rpm for 2 to 4 hours under nitrogen or inert gas atmosphere protection, so that the transition metal compounds are uniformly adhered to the surface of the core glass powder. Place the ball-milled powder in a tube furnace and heat-treat it at a temperature of 350°C to 450°C, below the softening point of the core glass, for 30 to 60 minutes under nitrogen or inert gas atmosphere protection, so that the outer shell material forms a slight sintered bond with the core surface.

[0072] Without damaging the chemical activity and crystal structure of the outer shell material, the outer shell and the surface of the core glass are bonded together with sufficient strength to resist peeling during subsequent processes. This ensures that the core glass does not soften or flow at this temperature, maintaining its original particle morphology and size distribution.

[0073] Finally, the mixture is allowed to cool naturally and then sieved to obtain composite glass powder with a core-shell structure and the desired particle size.

[0074] The composite glass powder obtained by the above method can be further used to prepare silver-coated copper electrode paste for photovoltaic / solar cells.

[0075] Step 3: Prepare the organic carrier according to the following mass percentages: based on the total mass of the organic carrier as 100%, organic solvent 75% to 90%, binder 6% to 12%, thixotropic agent 0.2% to 6%, leveling agent 0.1% to 5%, and defoamer 0.1% to 5%.

[0076] The organic solvent may be at least two of terpineol, diethylene glycol butyl ether acetate, 2-(2-butoxyethoxy)ethanol, and dibutyl phthalate.

[0077] The binder may be at least one of ethyl cellulose, phenolic resin, and acrylic resin.

[0078] The thixotropic agent is a polyamide wax.

[0079] The leveling agent can be at least one of silicone-based leveling agents and fluorocarbon-based leveling agents.

[0080] The defoamer can be at least one of silicone defoamers and non-silicone defoamers.

[0081] Step 4: The above-mentioned core-shell structured composite glass powder, silver-coated copper powder, and organic carrier are mixed in the following proportions: 75% to 85% silver-coated copper powder, 2% to 8% composite glass powder, and 12% to 20% organic carrier to prepare a conductive paste. After mixing with a planetary mixer, the paste is milled 5 to 7 times through a three-roll mill to ensure uniform dispersion, controlling the fineness to ≤10μm and the viscosity to 150 Pa·s to 250 Pa·s (25℃), thus obtaining a silver-coated copper back grid paste for photovoltaic / solar cells.

[0082] According to the present invention, the copper-plated silver paste

[0083] Another aspect of the present invention provides a silver-coated copper paste comprising composite glass powder, silver-coated copper powder, and an organic carrier as described in the present invention.

[0084] According to one embodiment of the present invention, the silver-coated copper paste, with the total mass of the silver-coated copper paste being 100%, has the following mass percentages of each component: 75%~85% silver-coated copper powder, 2%~8% composite glass powder, and 12%~20% organic carrier.

[0085] The composite glass powder in the copper-plated silver paste according to the present invention is a composite glass powder according to the present invention, thereby achieving the performance desired by the present invention as described above when it is formed into an electrode and applied to a solar cell. The copper-plated silver paste contains 2% to 8% of the composite glass powder according to the present invention, based on 100% of the total mass of the copper-plated silver paste. Exemplarily, the mass percentage of the composite glass powder can be 3%, 4%, 5%, 6%, 7%, etc.

[0086] The copper-coated powder in the copper-coated paste according to the present invention can be any conventional copper-coated powder in the art, and there are no particular limitations, as long as it does not adversely affect the effect of the composite glass powder of the present invention. Based on 100% of the total mass of the copper-coated paste, the copper-coated paste contains 75% to 85% copper-coated powder. Exemplarily, the mass percentage of copper-coated powder can be 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, etc.

[0087] The organic carrier in the copper-plated silver paste according to the present invention can be any conventional organic carrier in the art, and there are no particular limitations, as long as it does not adversely affect the effect of the composite glass powder of the present invention. Based on 100% of the total mass of the copper-plated silver paste, the copper-plated silver paste contains 12% to 20% organic carrier. Exemplarily, the mass percentage of the organic carrier can be 13%, 14%, 15%, 16%, 17%, 18%, 19%, etc.

[0088] According to one embodiment of the present invention, the silver-coated copper paste contains silver in the copper powder at a mass percentage of 10% to 40%. Exemplarily, the mass percentage of silver can be 15%, 20%, 25%, 30%, 35%, etc.

[0089] According to one embodiment of the present invention, the copper-plated silver paste has a particle size D50 of 1 μm to 3 μm. Exemplarily, the particle size D50 of the copper-plated silver powder can be 1.5 μm, 2 μm, 2.5 μm, etc.

[0090] According to one embodiment of the present invention, the fineness of the silver-coated copper paste can be less than or equal to 10 μm. Exemplarily, the fineness of the silver-coated copper paste can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, etc.

[0091] According to one embodiment of the present invention, the viscosity of the silver-coated copper paste can be from 150 Pa·s to 250 Pa·s. Exemplarily, the viscosity of the silver-coated copper paste can be 180 Pa·s, 200 Pa·s, 220 Pa·s, 240 Pa·s, etc. It should be noted that the viscosities mentioned in this specification are all viscosities at 25°C.

[0092] Solar cells according to the present invention

[0093] Another aspect of the invention provides a solar cell comprising electrodes prepared from a silver-coated copper paste according to the invention.

[0094] In addition to using the silver-coated copper paste according to the present invention to prepare electrodes, solar cells are prepared according to conventional methods.

[0095] Example

[0096] The invention will be described in more detail below by way of examples. However, the following examples are for illustrative purposes only and are not intended to limit the scope of the invention.

[0097] Example 1: Preparation of composite glass powder with a MoS2 outer shell and silver-coated copper paste containing it

[0098] Step 1: Preparation of core glass powder

[0099] Weigh each raw material according to the following mass percentages: 60% Bi2O3 (bismuth oxide Bi2O3, analytical grade, available from Sinopharm Chemical Reagent Co., Ltd.); 12% B2O3 (boron oxide B2O3, analytical grade, available from Sinopharm Chemical Reagent Co., Ltd.); 10% ZnO (Zinc oxide ZnO, analytical grade, content ≥99.0%, available from Sinopharm Chemical Reagent Co., Ltd.); 5% SiO2 (silicon dioxide, analytical grade, available from Sinopharm Chemical Reagent Co., Ltd.); 5% TeO2 (99.99% purity, available from Hangzhou Kaiyada Semiconductor Materials Co., Ltd., model TeO2-04); 3% TiO2 (TiO2, analytical grade, available from Sinopharm Chemical Reagent Co., Ltd.); 1% Ga2O3 (gallium oxide Ga2O3, analytical grade); 2% AlF3 (99.99% purity, available from Hunan Jingde New Material Technology Co., Ltd.); and 2% MnO2 (manganese dioxide, MnO2, analytical grade, available from Sinopharm Chemical Reagent Co., Ltd.).

[0100] The above raw materials were ground in an agate mortar for 30 minutes to ensure thorough mixing. The mixture was then placed in a corundum crucible and placed in a preheated electric furnace at 1250°C. The mixture was melted at high temperature for 1 hour, with the molten glass shaken every 30 minutes to ensure uniform melting of all components. The crucible was removed, and the molten glass was quenched in deionized water. Glass fragments were collected and dried in a 100°C oven for 12 hours. The dried glass fragments were then placed in a planetary ball mill and milled at 300 rpm for 5 hours. The resulting powder was sieved to obtain a core glass powder with a particle size D50 of 2.0 μm.

[0101] Step 2: Preparation of the MoS2 outer shell layer

[0102] Take 100 g of the core glass powder obtained in step 1, add 3 g of nano-MoS2 sheets (available from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., JP159, with a diameter of 200 nm to 500 nm and a thickness of approximately 1 nm), place in a ball mill, and ball mill at 400 rpm for 3 hours under an argon atmosphere to uniformly adhere the nano-MoS2 to the surface of the core glass powder. Place the ball-milled powder in a tube furnace, and under nitrogen protection, heat to 400 °C at a rate of 5 °C / min, hold for 45 minutes to allow the MoS2 to form a slight sintering bond with the core surface. After natural cooling, pass through a 300-mesh sieve to obtain a core-shell structured composite glass powder with a MoS2 outer shell, denoted as G1 in this paper. TEM observation shows that the thickness of this outer shell layer is in the range of approximately 60 nm to approximately 80 nm.

[0103] Step 3: Preparation of copper-plated silver paste

[0104] Prepare the organic carrier according to the following mass percentages: 60% terpineol, 25% diethylene glycol butyl ether acetate, 8% ethyl cellulose, 3% polyamide wax, 2% silicone leveling agent, and 2% silicone defoamer. Heat and stir in a water bath at 70°C until completely dissolved, then cool and defoam for later use. This mixture is denoted as V1.

[0105] The following components were weighed according to the following mass percentages: 80% silver-coated copper powder (available from Zhejiang Zhongchuan New Material Co., Ltd., ZC-Ag / Cu-OPS type silver-coated copper powder, with a silver content of 30% by mass and a particle size D50 of 1.5 μm), 5% composite glass powder G1 with a core-shell structure, and 15% organic carrier V1. The above materials were added to a planetary mixer and stirred at 500 rpm for 30 minutes for preliminary mixing. Then, the mixture was transferred to a three-roll mill and repeatedly ground 6 times to control the fineness ≤10 μm and the viscosity to be about 200 Pa·s (25℃), thus obtaining the silver-coated copper slurry of Example 1, denoted as S1.

[0106] Example 2: Preparation of composite glass powder with WP shell layer and silver-coated copper paste containing it

[0107] Step 1: Preparation of core glass powder

[0108] The raw materials were weighed according to the following mass percentages: 65% Bi2O3, 10% B2O3, 8% ZnO, 4% SiO2, 5% TeO2, 2% TiO2, 2% Ga2O3, 2% AlF3, and 2% MnO2. The preparation method of the core glass powder was the same as step 1 of Example 1, resulting in core glass powder with a D50 of 2.1 μm.

[0109] Step 2: Cover the WP with a case

[0110] 100 g of the aforementioned core glass powder was mixed with 5 g of nano-WP powder (WP powder particle size D50 approximately 80 nm), and placed in a ball mill. Under argon atmosphere, the mixture was ball-milled at 400 rpm for 3 hours to ensure uniform adhesion of the nano-WP particles to the surface of the core glass powder. The ball-milled powder was then placed in a tube furnace and heated to 420°C at a rate of 5°C / min under nitrogen atmosphere, and held for 40 minutes to allow a slight sintering bond between the WP and the core surface. After natural cooling, the powder was passed through a 300-mesh sieve to obtain a WP-coated core-shell composite glass powder, denoted as G2. TEM observation showed that the thickness of the outer shell layer ranged from approximately 50 nm to approximately 120 nm.

[0111] Step 3: Preparation of copper-plated silver paste

[0112] Prepare the organic carrier according to the following mass percentages: 55% 2-(2-butoxyethoxy)ethanol, 30% dibutyl phthalate, 7% phenolic resin, 4% polyamide wax, 2% fluorocarbon leveling agent, and 2% non-silicone defoamer. Heat and stir in a water bath at 75°C until completely dissolved, cool and allow to stand to remove bubbles, and then set aside as V2.

[0113] The slurry was prepared using the same method as step 3 of Example 1. The composite glass powder with a core-shell structure was G2, the organic carrier was V2, and the final silver-coated copper slurry was denoted as S2.

[0114] Example 3: Preparation of composite glass powder with a mixed outer shell layer and silver-coated copper paste containing it

[0115] Step 1: Preparation of core glass powder

[0116] The raw materials were weighed according to the following mass percentages: 58% Bi2O3, 12% B2O3, 9% ZnO, 5% SiO2, 6% TeO2, 3% TiO2, 2% Ga2O3, 3% AlF3, and 2% MnO2, totaling 100%. The preparation method of the core glass powder was the same as step 1 in Example 1, resulting in core glass powder with a D50 of 1.9 μm.

[0117] Step 2: Mixing the outer shell layer

[0118] Take 100g of the core glass powder, add 3g of nano-MoS2 flakes and 3g of nano-WP powder, place in a ball mill, and ball mill at 400 rpm for 3 hours under argon atmosphere protection to ensure that nano-MoS2 and WP are uniformly adhered to the surface of the core glass powder. Place the ball-milled powder in a tube furnace, and heat to 410℃ at 5℃ / min under nitrogen protection, hold at that temperature for 45 minutes. After natural cooling, pass through a 300-mesh sieve to obtain a composite glass powder with a core-shell structure coated with MoS2 / WP, denoted as G3. TEM observation shows that the thickness of the outer shell layer is in the range of approximately 60 nm to approximately 150 nm, and thin, flake-like, wrinkled, shallow-contrast, and translucent MoS2 nanosheets, as well as solid, well-defined spherical or near-spherical particles and deeply contrasted WP nanoparticles coexist on the surface of the core glass powder.

[0119] Step 3: Preparation of copper-plated silver paste

[0120] Prepare the organic carrier according to the following mass percentages: 50% terpineol, 25% diethylene glycol butyl ether acetate, 10% ethyl cellulose, 5% polyamide wax, 5% silicone leveling agent, and 5% silicone defoamer, totaling 100%. Heat and stir in a water bath at 70°C until completely dissolved, then allow to stand to remove bubbles and set aside. This mixture is designated as V3.

[0121] The slurry was prepared using the same method as step 3 of Example 1. The composite glass powder with a core-shell structure was G3, the organic carrier was V3, and the final silver-coated copper slurry was denoted as S3.

[0122] Comparative Example 1: Conventional glass powder, without an outer shell layer

[0123] The core glass powder, using the same formulation as in step 1 of Example 1, was used directly as glass powder without any outer shell coating treatment and is denoted as D1. The organic carrier used is V1. The silver-coated copper paste was prepared using the same method as in step 3 of Example 1 and is denoted as DS1.

[0124] Comparative Example 2: Composite glass powder with a P2O5 outer shell prepared by a simple physical mixing method and containing thereof Preparation of silver-plated copper paste

[0125] 100 grams of core glass powder with the same formulation as in step 1 of Example 1 was simply physically mixed with 5 grams of P2O5 powder (P2O5 powder particle size D50 approximately 2 μm) without ball milling or heat treatment to obtain composite glass powder D2. The organic carrier used was V1. A silver-coated copper paste, denoted as DS2, was prepared using the same method as in step 3 of Example 1.

[0126] Comparative Example 3: Composite glass powder with a SiO2 outer shell prepared by an in-situ method and a silver foil containing it. Preparation of copper paste

[0127] 100 g of the core glass powder was dispersed in 500 mL of ethanol. An ethanol solution of tetraethyl orthosilicate (TEOS) (10 g TEOS dissolved in 50 mL of ethanol) was prepared and slowly added dropwise to the core glass powder dispersion. Simultaneously, ammonia was added dropwise to adjust the pH to 9-10. The mixture was stirred at 50 °C for 4 hours. After centrifugation, washing, drying at 80 °C for 12 hours, and calcining at 500 °C for 2 hours, a SiO2-coated core-shell composite glass powder, denoted as D3, was obtained. TEM observation showed that the thickness of the outer shell layer ranged from approximately 40 nm to approximately 100 nm.

[0128] The slurry was prepared using the same method as step 3 of Example 1. The composite glass powder with a core-shell structure was D3, and the organic carrier was V1. The final silver-coated copper slurry was denoted as DS3.

[0129] Experimental Example 1: High-temperature microscopy and contact angle tests were performed on the composite glass powders or conventional glass powders in the above embodiments and comparative examples. The results are shown in [Figure Number]. Figure 1 and Figure 2 .

[0130] Depend on Figure 1 It can be seen that the characteristic temperature of the composite glass powder with all outer shells is higher than that of the sample without an outer shell. This is because the outer shell forms a physical barrier on the glass surface, which hinders the thermal movement of the glass network.

[0131] The SiO2-coated Comparative Example 3 exhibits the most significant increase in characteristic temperature. This is because SiO2 and the core glass belong to the same oxide glass system, forming a strong chemical bond through bridging oxygen bonds during heat treatment. This results in a denser, more cross-linked monolithic glass phase, requiring a higher temperature for softening and flow. In contrast, MoS2 and WP have poor chemical compatibility with the core glass, with interfacial bonding primarily based on physical adhesion, failing to form strong chemical bonds. This weak bonding prevents the glass from excessively increasing its softening temperature, thus fulfilling the function of capturing copper ions while ensuring that the slurry can fully melt at conventional sintering temperatures, etching the passivation layer and forming good ohmic contacts.

[0132] Depend on Figure 2 It can be seen that by coating MoS2 and / or WP, an active layer with moderate surface energy is formed on the surface of the composite glass powder, which significantly reduces the wetting angle of the glass melt on the silicon wafer surface and improves the printability and sintering contact uniformity of the paste. Among them, Example 3 with mixed coating shows the best synergistic wetting effect.

[0133] Experimental Example 2: The silver pastes prepared in the above examples and comparative examples were tested online. Different pastes were printed on the back of TOPCon cells using a screen printing machine, dried, and then sintered in a chain furnace at a peak temperature of 720°C. The contact resistance of each paste after sintering was tested using the TLM method (see: China Photovoltaic Industry Association T / CPIA 0051-2023 "Test Method for Contact Resistivity of Metal Electrodes in Crystalline Silicon Photovoltaic Cells - Transmission Line Model Method (TLM)"). The results are shown in Table 1.

[0134] Table 1: TLM test results of different samples

[0135] As can be seen from Table 1, the contact resistivity of Examples 1-3 is close to that of Comparative Example 1. Among them, Example 3 has the lowest contact resistivity, which is closest to the contact resistivity of the uncoated Comparative Example 1.

[0136] In contrast, the contact resistivity of Comparative Example 2 was significantly higher. This is because P2O5, as an oxide, reacts with copper ions to form copper phosphate, which has poor conductivity and insufficient thermal stability, resulting in weak chemical trapping ability. In addition, physical mixing leads to uneven distribution of active components, making it impossible to form a continuous and effective trapping barrier. At the same time, the physically mixed P2O5 may generate insulating products, which deteriorates the contact.

[0137] The contact resistivity of Comparative Example 3 is 4.195 mΩ·cm. 2 The resistivity of Comparative Example 3 is also higher than that of the embodiments of the present invention. The reason why the performance of Comparative Example 3 is worse than that of the embodiments of the present invention is that the homogeneous strong fusion of SiO2 and core glass powder leads to an upward shift in the sintering temperature window, resulting in insufficient glass melting and reduced ability to etch the passivation layer at conventional process temperatures; at the same time, SiO2 lacks chemically active sites and cannot synergistically optimize the contact interface.

[0138] By comparing Examples 1 to 3 of the present invention with Comparative Example 3, it can be confirmed that the present invention uses MoS2 and / or WP, which have moderate chemical inertness and core glass and active trapping sites, as the outer shell layer, which has the advantage of ensuring the copper ion trapping function without deteriorating the sintering contact performance.

[0139] Experimental Example 3: Six groups of samples prepared for the examples and comparative examples underwent PID testing (following GB / T 6495.9-2022). Twenty solar cells were prepared using each paste, and the average value was used for testing. The PID testing conditions were as follows: the solar cells were placed in the PID testing system, a -1000V bias voltage was applied, the ambient temperature was 85℃, the relative humidity was 85%, and the testing time was 96 hours. The photoelectric conversion efficiency before and after PID treatment was tested, and the results are shown in Table 2.

[0140] Table 2: Comparison of battery efficiency before and after PID testing using different slurries

[0141] As shown in Table 2, the batteries prepared in Examples 1-3 of this invention all exhibited efficiency degradation rates below 3% after PID testing, significantly better than those in Comparative Examples 1-3. Among them, Example 3 showed the lowest degradation rate, at only 2.15%, indicating that the mixed coating of MoS2 and WP has the best synergistic anti-PID effect.

[0142] This confirms that the present invention effectively suppresses the migration of copper to the silicon substrate by efficiently capturing diffused copper ions through the MoS2 and / or WP shell layer, thereby significantly improving the reliability of the solar cells prepared by silver-coated copper paste.

[0143] Unless otherwise specified, the raw materials and equipment used in this invention are all commonly used in the art; unless otherwise specified, the methods and process steps used in this invention are all conventional methods and process steps in the art.

[0144] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any modifications, alterations, and equivalent transformations made to the above embodiments based on the technical spirit of the present invention shall still fall within the scope of protection claimed in this application.

Claims

1. A composite glass powder, characterized in that, The composite glass powder has a core-shell structure, comprising a core glass powder and an outer shell layer covering the surface of the core glass powder, wherein the outer shell layer contains transition metal chalcogenides and / or transition metal phosphorus compounds.

2. The composite glass powder according to claim 1, characterized in that, The transition metal chalcogenide includes one or more selected from molybdenum disulfide, tungsten disulfide, molybdenum diselenide, and tungsten diselenide; And / or, The transition metal phosphorus compound includes one or more selected from tungsten phosphide, molybdenum phosphide, cobalt phosphide, and nickel phosphide; And / or, The core glass powder is a lead-free glass powder comprising Bi2O3, B2O3, ZnO and SiO2.

3. The composite glass powder according to claim 1 or 2, characterized in that, The mass of the outer shell layer is 1% to 10% of the mass of the core glass powder; And / or, The thickness of the outer shell layer is 10 nm to 200 nm.

4. The composite glass powder according to claim 1 or 2, characterized in that, The softening point of the core glass powder is 400℃~600℃; And / or, The particle size D50 of the core glass powder is 1.0 μm to 3.0 μm; And / or, Based on the total mass of the core glass powder as 100%, the composition and mass fraction of each component of the core glass powder are as follows: Bi2O3 55%~75%, B2O3 8%~18%, ZnO 5%~15%, SiO2 3%~8%, TeO2 0%~20%, TiO2 2%~4%, Ga2O3 0.3%~5%, AlF3 2%~6%, MnO2 1%~6%, and additives 0%~4%, wherein the additives are one or more of CeO2 and MoO3.

5. A method for preparing composite glass powder as described in any one of claims 1 to 4, characterized in that, The method includes the following steps: (1) Provide core glass powder; (2) The core glass powder is mixed with a transition metal chalcogenide and / or a transition metal phosphorus compound, so that the transition metal chalcogenide and / or the transition metal phosphorus compound adhere to the surface of the core glass powder, and then heat-treated in a nitrogen or inert gas atmosphere to obtain the composite glass powder with a core-shell structure. or, The core glass powder is dispersed in a solvent, and precursors of transition metal chalcogenides and / or transition metal phosphogenides are added. The precursors are then attached to the surface of the core glass powder by chemical deposition, followed by reduction heat treatment to obtain the composite glass powder with a core-shell structure.

6. The method for preparing composite glass powder according to claim 5, characterized in that, The core glass powder is prepared by the following method: the components of the core glass powder are mixed evenly, then heated to melt the components evenly to obtain a glass melt, the glass melt is then quenched to form glass fragments, and finally the glass fragments are ball-milled and sieved to obtain the core glass powder with the desired particle size. And / or, The transition metal chalcogenide and / or the transition metal phosphorus compound are mixed by ball milling to adhere to the surface of the core glass powder. The process conditions of the ball milling include: nitrogen or inert gas atmosphere, ball milling speed of 300 rpm to 500 rpm, and ball milling time of 2 h to 4 h. And / or, When transition metal chalcogenides and / or transition metal phospholipids are used as raw materials, the heat treatment temperature is 350℃~450℃ and the time is 30 min~60 min; when transition metal chalcogenides and / or transition metal phospholipids precursors are used as raw materials, the reduction heat treatment temperature is 350℃~450℃ and the time is 30 min~60 min.

7. A silver-coated copper paste, characterized in that, The silver-coated copper paste comprises composite glass powder, silver-coated copper powder, and organic carrier as described in any one of claims 1 to 4.

8. The silver-coated copper paste according to claim 7, characterized in that, Based on the total mass of the silver-coated copper paste as 100%, the mass percentages of each component in the silver-coated copper paste are as follows: 75%~85% silver-coated copper powder, 2%~8% composite glass powder, and 12%~20% organic carrier.

9. The silver-coated copper paste according to claim 8, characterized in that, The silver content in the silver-coated copper powder is 10% to 40% by mass. And / or, The particle size D50 of the silver-coated copper powder is 1 μm to 3 μm; And / or, The fineness of the silver-coated copper paste is less than or equal to 10 μm and the viscosity is 150 Pa·s to 250 Pa·s.

10. A solar cell, characterized in that, The solar cell comprises an electrode prepared from a silver-coated copper paste according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Silicon solar cell electrode silver coated copper sizing agent and preparing method thereof

    CN104157331A